2015
DOI: 10.1163/15685373-12342164
|View full text |Cite
|
Sign up to set email alerts
|

Examining Special Patient Rituals in a Chinese Cultural Context: A Research Report

Abstract: Is reasoning about religious ritual tethered to ordinary, nonreligious human reasoning about actions? E. Thomas Lawson and Robert N. McCauley’s ritual form hypothesis (rfh) constitutes a cognitive approach to religious ritual – an explanatory theory that suggests people use ordinary human cognition to make specific predictions about ritual properties, relatively independent of cultural or religious particulars. Few studies assess the credibility ofrfhand further evidence is needed to generalize its predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…These descriptions were then coded and analyzed, using each ritual generated as the unit of analysis, and conformed to RFH predictions to a significantly greater degree than would be expected by chance. Using a similar methodology, Hornbeck, Bentley, and Barrett (2015) found that the Taoist, Buddhist, and traditional Chinese rituals described by ethnically Chinese informants in Singapore likewise almost perfectly conformed to RFH predictions concerning repeatability and reversibility. Similarly, Barrett et al.…”
Section: Rfh Summarizedmentioning
confidence: 91%
See 1 more Smart Citation
“…These descriptions were then coded and analyzed, using each ritual generated as the unit of analysis, and conformed to RFH predictions to a significantly greater degree than would be expected by chance. Using a similar methodology, Hornbeck, Bentley, and Barrett (2015) found that the Taoist, Buddhist, and traditional Chinese rituals described by ethnically Chinese informants in Singapore likewise almost perfectly conformed to RFH predictions concerning repeatability and reversibility. Similarly, Barrett et al.…”
Section: Rfh Summarizedmentioning
confidence: 91%
“…A limited number of studies have assessed RFH empirically (e.g., Barrett and Lawson 2001; Malley and Barrett 2003; see also Barrett 2004; Hornbeck, Bentley, and Barrett 2015; Barrett et al. 2017) and used it to analyze historic patterns (e.g., Vial 2004).…”
Section: Rfh Summarizedmentioning
confidence: 99%